Response of Broiler Chicks to Graded Levels of Alphamune G Supplementation - Bolu, S.A.; Ojo, V.; Oyeleke, B.A.; Ajiboye, A.O.; Sambo, A. Baa; Oluyemi, O. (International Journal of Poultry Science, 2008)
A study was conducted on 120 day-old broiler chicks fed graded levels of Alphamune G (0.00, 0.04, 0.05 and 0.06%) in a Completely Randomized Design. The experiment was conducted for 8 weeks. Feed intake and weight gain were significantly influenced (p<0.05) by the inclusion levels of Alphamune G. Broiler chicks fed 0.04% inclusion level of Alphamune G had the highest weight gain (35.85 g) with the least feed to gain ratio (2.36). Carcass characteristics also revealed broiler chicks on 0.04% inclusion of Alphamune G to be significantly better than the control diet in weight of keel, drumstick and thigh (20.65, 13.79 and 12.22 g, respectively). Heamatological values did not show any significant effect (p>0.05) except in PCV value where 0.04% inclusion of Alphamune had significantly lower value (31.00%). However all values fall within the normal range. Histological studies revealed morphological changes in broilers fed Alphamune G supplemented diet viz- a-viz the control diet. Alphamune G at 0.04% inclusion in diets of broilers may help improve performance.